Growth and survival rate of post-puerulus spiny lobster Panulirus homarus at different rearing systems - MUHAMMAD QUSTAM SAHIBUDDIN; IRZAL EFFENDI; IIS DIATIN; TATAG BUDIARDI; MIA SETIAWATI (Society for Indonesian Biodiversity, 2025)
Abstract. Sahibuddin MQ, Effendi I, Diatin I, Budiardi T, Setiawati M. 2025. Growth and survival rate of post-puerulus spiny lobster Panulirus homarus at different rearing systems. Biodiversitas 26: 6285-6304. Mariculture of lobsters utilizes Floating Net Cages (FNC), Submersible Net Cages (SNC), and Bottom Net Cages (BNC). This study analyzed the growth and Survival Rate (SR) of post-puerulus Panulirus homarus in these three rearing systems. Post-puerulus individuals (0.86±0.06 cm carapace length; 0.28±0.04 g body weight) were reared in net cages (height 0.8 m; diameter 1 m) at a stocking density of 100 individuals cage-1, with three replicates. The lobsters were fed a moist diet once daily (4:00-5:00 PM). The different rearing system significantly influenced specific growth rate (SGR), Absolute Growth Rate (AGR), total molting, Feed Conversion Ratio (FCR), Intermoult Period (IMP), and SR. The FNC and BNC treatments demonstrated the highest SGR (p: 0.012), at 2.80±0.022% day-1 and 2.76±0.078% day-1, respectively. These treatments also produced the highest AGR (p: 0.013), at 0.07±0.004 g day-1 and 0.06±0.006 g day-1, respectively. The highest total molting (p: 0.025) occurred in the FNC (45.33±9.074 times cage-1) and BNC (43.67±5.033 times cage-1) treatments. The BNC treatment achieved the lowest FCR (7.34±0.372), which was not significantly different from FNC but was significantly lower than SNC (p: 0.032). The FNC treatment resulted in the shortest IMP (14.37±0.38 days, p: 0.000), while the highest SR was observed in the BNC treatment (71.00±2.00%, p: 0.000). Additionally, the lowest glucose (14.14±1.58 mg dL-1, p: 0.031) and total hemocyte count (1.81±0.29x107 cells mL-1, p: 0.000) were recorded in the BNC treatment. These findings indicate that the BNC treatment provided the highest SR and the lowest stress response for post-puerulus P. homarus.